Successful treatment with afatinib following the failure of osimertinib rechallenge with osimertinib-induced interstitial lung disease: A case report. (2021) - Sato, Yozo; Sekine, Akimasa; Hagiwara, Eri; Sato, Midori; Yamaya, Takafumi; Asaoka, Masato; Higa, Katsuyuki; Ikeda, Satoshi; Baba, Tomohisa; Komatsu, Shigeru; Iwasawa, Tae; Ogura, Takashi
Abstract: Herein, we report the case of an 84-year-old woman with epidermal growth factor receptor ( EGFR ) mutation exon 19 deletion postoperative recurrent lung adenocarcinoma. Osimertinib was administered as a first-line treatment; however, she was urgently admitted to our hospital due to dyspnea on the 46th day. Chest computed tomography revealed bilateral diffuse ground-glass opacities (GGOs) suggestive of grade 3 osimertinib-induced interstitial lung disease (ILD). After discontinuation of osimertinib in combination with short-term corticosteroid therapy, widespread GGOs were promptly resolved. As the disease gradually deteriorated after discontinuation of osimertinib, we administered osimertinib (80 mg every other day) followed by careful observation. However, bilateral GGOs re-appeared on the 15th day, and the diagnosis of osimertinib-induced ILD was established. After the improvement in ILD following corticosteroid therapy, afatinib was administered as salvage therapy, resulting in desirable control of lung cancer without any relapse of ILD. Our results indicate that afatinib would be a promising alternative treatment option even in patients who develop osimertinib-induced ILD and experience failure of osimertinib rechallenge.